Economic valuation of the ecosystem of the high Andean hydrographic basin tributary of the Chumbao River, through multicriteria analysis - Barrial Lujan, A. I. (2026)
Environmental wealth is the main basis of the social, cultural and economic development of a country, but if there is an absence of the valuation of these natural resources, it can lead to a disproportionate usufruct that causes the deterioration of the ecosystem and even collateral effects of human health. This research aimed to know the total economic value of the ecosystem of the high Andean water basin tributary of the Chumbao River, located between 2000 to 4800 meters above sea level belonging to the province of Andahuaylas, Apurimac region in Perú. The valuation procedure consisted of using the analytical method of multicriteria valuation applying the concept of Total Economic Value, which involved direct and indirect uses related to environmental assets, in which a collective panel of people from different training disciplines (experts) participated, which were made up of researchers, engineers, public officials, farmers and ecologists who had extensive knowledge about the environmental asset. of the geographical area in reference; and once the paired comparison survey was done, the total economic value was quantified up to three amounts, so the respondents were formed into three statistically significant segments (SIG<0.05). The cluster (1): assigned a weighting that quantifies to an economic value of USS 4,359,179,489.46; followed by cluster (2): an intermediate value of USS 4,029,902,444.41 and cluster (3): assigned a lower value to USS 774,163,167.16. Thus, it follows that, on average, 51.78% equals value in use and 48.21% equals value in non-use, respectively. This value expressed as an interval reflects the environmental ethical positions of the groups and makes available as an indicator to government authorities and society in order to exercise actions of environmental sustainability high andean.